Acid Gas to Syngas (AG2S™) technology applied to solid fuel gasification: Cutting H2S and CO2 emissions by improving syngas production. (15th December 2016) - Bassani, Andrea; Pirola, Carlo; Maggio, Enrico; Pettinau, Alberto; Frau, Caterina; Bozzano, Giulia; Pierucci, Sauro; Ranzi, Eliseo; Manenti, Flavio
Highlights: Coal gasification with improved yield and reduced emissions. AG2S™ process converts H2 S and CO2 into syngas, elemental sulfur and water. Techno-economic simulation of AG2S™ process is carried out. Industrial case-study on the Sotacarbo S.p.A. gasification pilot plant is proposed. Abstract: The paper deals with the application of the novel Acid Gas To Syngas (AG2S™) technology to the gasification of solid fuels. The AG2S technology is a completely new effective route of processing acid gases: H2 S and CO2 are converted into syngas (CO and H2 ) by means of a regenerative thermal reactor. To show the application of the AG2S technology, modeling and simulation advances for gasification systems are initially discussed. The multi-scale, multi-phase, and multi-component coal gasification system is described by means of detailed kinetic mechanisms for coal pyrolysis, char heterogeneous reactions and for successive gas-phase reactions. These kinetic mechanisms are then coupled with transport resistances resulting in first-principles dynamic modeling of non-ideal reactors of different types (e.g., downdraft, updraft, traveling grate), also including the catalytic effect of ashes. The generalized approach pursued in developing the model allows characterizing the main phenomena involved in the coal gasification process, including the formation of secondary species (e.g., COS, CS2 ). This tool is here further validated on literature data and, then, adopted to demonstrate the AG2S effectiveness, where H2 S and CO2 emissions are reduced with an increase of syngas production. The resulting process solution is more economically appealing with respect to the traditional Claus process and finds several application areas.